Hubungan Penerapan Water, Sanitation And Higiene (WASH) dengan Kejadian Stunting di Wilayah Pesisir: Systematic Review - Syifa Mauliddina; Budi Hartono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Stunting remains a significant public health problem in developing countries and is closely associated with inadequate environmental conditions, particularly those related to water, sanitation, and hygiene (WASH). This systematic review aims to examine the relationship between WASH practices and the prevalence of stunting among children under five years of age in coastal areas. A total of 11 studies published between 2016 and 2025 were selected from databases such as PubMed, Scopus, ScienceDirect, ProQuest, and other external sources using the PRISMA approach and the PEOS framework. Findings from countries including Pakistan, Bangladesh, India, and Indonesia consistently indicate that poor WASH conditions significantly increase the risk of stunting. Inadequate sanitation facilities, lack of access to safe drinking water, and poor hygiene practices were identified as major contributing factors. Several studies from Indonesia reported high odds ratios for stunting among children exposed to unsafe water and inadequate sanitation, with increased risks ranging from 2.66 to 6.37 times. Some studies suggest that improved sanitation has a stronger association with reduced stunting than improved access to drinking water. Most included studies employed cross-sectional designs, highlighting significant correlations, although causal inferences remain limited. Therefore, long-term integrated interventions that ensure access to clean water, adequate sanitation, and hygiene education should be prioritized in public health strategies, particularly in vulnerable coastal communities.